Conference on the Reception of Baltic Literature Abroad atthe University of Greifswald - Baravykaitė, Alina (Respectus Philologicus, 2025)
On 17 June 2025, an international scientific conference entitled “Small” Literatures in the Big World: Worldwide Reception of Latvian and Lithuanian Literature in Translation was held at the University of Greifswald, at which literary scholars and translators from five countries presented their papers. This was the second conference on translation theory and practice to be organised by the Department of Baltic Studies. The impetus for the conference was the growing attention to translations of Baltic literature into foreign languages, ranging from translation support programmes to awards for translators and translations from Lithuanian and Latvian abroad, which are comparable to the recognition of translated literature. The primary objective of the conference was to explore the role of translators, publishers, and readers in the process of dissemination and perception of translated Baltic fiction. The presentations were not limited to specific literary genre, time period or artistic value, and did not delve into the concept of “Small” literature, for which there is currently no universally accepted definition. The selection of the reception topic was also motivated by the perception that translations of Baltic literature, along with their nominations and awards, are associated with a broad dissemination and reception of Baltic literature.
Keywords: conference; reception of Baltic literature abroad; University of Greifswald